(untitled) (Psicologia USP, 2008)
A defender of social causes and a poetic paladin crusading against injustice and inequality, Ecléa Bosis research into the reading habits of circa 50 women workers led to her book, Cultura Popular e Cultura de Massa: Leituras de Operárias, where she explores their access to books and the imaginary, their lives and how industrial society deprives them of artistic and literary creativity, despite their thirst for knowledge and self expression.